1993
DOI: 10.1161/01.str.24.4.532
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in first-ever stroke in the carotid artery territory seen within 6 hours after onset.

Abstract: Background and Purpose:We sought to detect prognostic factors related to functional outcome during the first 6 hours after a first-ever stroke in the carotid artery territory.Methods: All patients with these characteristics seen during a 3-year period were included. Outcome was evaluated according to a modified Rankin scale. The following variables were examined at univariate analysis: sex, age, severity of deficit at entry and at day 7, level of consciousness at entry, time after symptom onset, history of smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
0
5

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 35 publications
5
40
0
5
Order By: Relevance
“…53 It was shown that parenchymal hypodensity is a reliable sign of irreversible brain tissue damage. 12,15,22,54 We could not identify clinical variables as independent predictors for early cerebral death after ischemic stroke. Censori et al 12 found among 172 patients with ischemic stroke admitted within 6 hours only a Canadian Neurological Scale score Ͻ6.5 at entry and atrial fibrillation associated with a significant handicap or death after 30 days.…”
Section: Berrouschot Et Al December 1998mentioning
confidence: 88%
See 1 more Smart Citation
“…53 It was shown that parenchymal hypodensity is a reliable sign of irreversible brain tissue damage. 12,15,22,54 We could not identify clinical variables as independent predictors for early cerebral death after ischemic stroke. Censori et al 12 found among 172 patients with ischemic stroke admitted within 6 hours only a Canadian Neurological Scale score Ͻ6.5 at entry and atrial fibrillation associated with a significant handicap or death after 30 days.…”
Section: Berrouschot Et Al December 1998mentioning
confidence: 88%
“…Only a few studies included data from the first 6 hours after stroke onset, [12][13][14][15] and the findings are contradictory. 16,17 Many studies did not differentiate between hemorrhagic and ischemic stroke 2,18,19 or were retrospective.…”
mentioning
confidence: 99%
“…This confirms previous findings in the general stroke population. 3,10,[21][22][23][24] It should be emphasized that function was defined by the ability to perform basic activities of daily living as measured by the BI. An influence on the ability to perform instrumental activities of daily living or higher cognitive functions can therefore not be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were then classified as dependent if exhibiting a moderate to severe handicap (mRS Ն3) or independent with no to mild handicap (mRS Յ2). 20 Finally, mortality was recorded over a median follow-up period of 1508 days (range, 9 to 2656 days) after acute ictus. To ensure data capture as complete as possible, mortality outcome was assessed from a number of sources, including hospital medical records, hospital information systems, general practitioner records, and Health Authority returns from general practitioners and from the registrar for births, marriages, and deaths.…”
Section: Protocolmentioning
confidence: 99%